Rocznik Solecki, t. III, Wyd. Muzeum Solca im. Księcia Przemyśla w Solcu Kujawskim, Solec Kujawski 2012 (Kronika Bydgoska, 2012)
In September 2012, the third number of the Solec Kujawski Annual appeared in print, published by the Duke Przemysł Solec Museum in Solec Kujawski. The periodical aims at presentation of the history of the town and its vicinity. The publication includes articles, remembrances of well-known Solec Kujawski residents, and a chronicie of the year 2011. The authors of the publication in this year’s volume are: Jadwiga Bretes discussing issues conceming Catholic organisations active in Solec Kujawski in the inter-war period, and Bolesław Boczkaja presenting events that took place in Otorowo during World War Two. Łukasz Wojtecki prepared a work on the economic situation of Solec Kujawski from the second half of the 19lh century to the year 1952, and Marcin Hlebionek madę a source analysis of two documents describing how penalties were dispensed in the town in the early 17th century. The finał article was written by Marta Kliś describing the archaeological operations of the Solec Museum. She is also the author of the chronicie. The annual includes also remembrances of eminent Solec Kujawski residents who died in 2011, i.e. Mayor Antoni Nawrocki and Mr Roman Zakrzewski.